1996
DOI: 10.1007/s00585-996-1025-3
|View full text |Cite
|
Sign up to set email alerts
|

Travelling convection vortices in the ionosphere map to the central plasma sheet

Abstract: Abstract. We investigate the magnetospheric domain responsible for the generation of ionospheric travelling convection vortices (TCV) by comparing the location of the TCV to the locations of the low-altitude particle-precipitation boundaries deduced from the DMSP satellite measurements. For three very well documented TCV events we are able to identify suitable satellite passes, in the sense that for each event we can identify two to three passes occurring close to the TCV observation in both time and space. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Yahnin and Moretto, 1996) show that events appear to maximise in their magnetic ®eld variations 1±2 o equatorward of the cusp precipitation, and indicate that many TCVs are ®eld-aligned current systems that are evolving very rapidly in space and time. Therefore, some TCVs may be another ionospheric manifestation of the proposed new current system.…”
Section: Implications and Interpretation Of The New Observationsmentioning
confidence: 90%
“…Yahnin and Moretto, 1996) show that events appear to maximise in their magnetic ®eld variations 1±2 o equatorward of the cusp precipitation, and indicate that many TCVs are ®eld-aligned current systems that are evolving very rapidly in space and time. Therefore, some TCVs may be another ionospheric manifestation of the proposed new current system.…”
Section: Implications and Interpretation Of The New Observationsmentioning
confidence: 90%
“…In the recent work of Yahnin et al (1997) and Yahnin and Moretto (1996) it was demonstrated for a few case studies that the position of the centres of the ®eld-aligned currents driving ionospheric travelling convection vortices (TCV) coincide with regions of plasmasheet-type precipitation as identi®ed by particle precipitation data from the DMSP satellites. This result was founded on the Newell scheme (Newell et al, 1991) for the identi®cation of plasma regions.…”
Section: Introductionmentioning
confidence: 99%
“…The vortices are typically on the order of 1000 km in extent in the ionosphere and propagate at several km/sec in the anti-sunward direction. TCVs appear to occur on closed field lines, but the mapping of the field to structures such as the magnetopause, the low-latitude boundary layer (LLBL), the boundary of the central plasma sheet, or the CPS itself [Yahnin and Moretto, 1996] is under debate.…”
mentioning
confidence: 99%